Implementation of PjBL-STEM to Improve Students' Creative Thinking Skills On Static Fluid Topic - Asep Saefullah; Andri Suherman; Riska Tri Utami; Ganesha Antarnusa; Diana Ayu Rostikawati; Robby Zidny (STKIP Singkawang, 2021)
This research aims to investigate the influence of Project-Based Learning (PjBL)- Science, Technology, Engineering, and Mathematics (STEM) on Students' Creative Thinking Skills. The research method was quasi-experiment using a nonequivalent control group design. Samples were taken using purposive sampling technique from two of 11th-grade science classes as an experimental and a control groups. This study used a test instrument of creative thinking skills. Research data were analyzed using SPSS and Microsoft Excel software. Hypothetical test results were assessed using independent sample t-test, obtained sig value (2-tailed) = 0.01 indicating sig value < 0.05. According to statistical analysis, there is a significant difference between the control class and the experiment class. The n-gain value was obtained with a score of 0.59 (a medium category). This result shows that the application of PJBL-STEM can improve students' creative thinking skills in the static fluid topic (Pascal law).